2005
DOI: 10.3998/ark.5550190.0007.312
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0)-catalyzed synthesis of pyridines from β-acetoxy-γ,δ-unsaturated ketone oximes

Abstract: Pyridines are synthesized from β-acetoxy-γ,δ-unsaturated ketone O-acetyloximes by treatment with triethylamine and a catalytic amount of Pd(PPh 3 ) 4 in toluene at 120 o C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…The regiochemistry of the first coupling was proven by stopping the reaction after the first coupling and then removing the second bromine using catalytic hydrogenation. The resulting product exhibited spectral properties identical to that reported for 2-(4‘-methoxyphenyl)pyridine 3 Double-Couplings of 2,3-Dibromopyridine entry a ArAr‘yield b (%) 1 pMeOC 6 H 4 Ph (86) 2 Ph pMeOC 6 H 4 (72) 3 Ph Heptenyl 58 4 pMeOC 6 H 4 pAcC 6 H 4 43 (78) 5 3,4,5-TriMeOC 6 H 4 3-MeO-4-iPrOC 6 H 4 28 a Base = 2-M Na 2 CO 3 , solvent =toluene/EtOH (3:1 v/v).…”
Section: Results and /Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The regiochemistry of the first coupling was proven by stopping the reaction after the first coupling and then removing the second bromine using catalytic hydrogenation. The resulting product exhibited spectral properties identical to that reported for 2-(4‘-methoxyphenyl)pyridine 3 Double-Couplings of 2,3-Dibromopyridine entry a ArAr‘yield b (%) 1 pMeOC 6 H 4 Ph (86) 2 Ph pMeOC 6 H 4 (72) 3 Ph Heptenyl 58 4 pMeOC 6 H 4 pAcC 6 H 4 43 (78) 5 3,4,5-TriMeOC 6 H 4 3-MeO-4-iPrOC 6 H 4 28 a Base = 2-M Na 2 CO 3 , solvent =toluene/EtOH (3:1 v/v).…”
Section: Results and /Discussionsupporting
confidence: 55%
“…Interestingly, in the case of reactions using DMF as the solvent, the major product with phosphine-ligated palladium catalysts was not coupling product 1 , but rather the dehalogenated coupling product 2 (Scheme ). Conveniently, this byproduct enabled us to confirm the expected regiochemistry of these couplings, since a comparison of the 1 H NMR spectrum of 2 with that reported in the literature showed that the two were identical . The mechanism of this dehalogenation remains unclear.…”
Section: Results and /Discussionsupporting
confidence: 53%
“…To our knowledge, the reaction in Scheme 2 represents the first example of producing pyridinyl derivative from g,d-unsaturated ketone oxime derivatives in the absence of a bacetoxy or alkoxy group or an a,b-double bond, the functionalities so far having shown to be indispensable for generating 9 and its analogues. 1a, 9 We speculated that the regiochemical bias observed in our case may be attributed to the unique coordination nature and/or the steric effect of the diethylphosphinyl group. Currently, the studies to disclose the mechanistic intricacies of the regiochemistry are being carried out by us.…”
mentioning
confidence: 72%
“…5- exo cyclization and subsequent isomerization allowed access to substituted pyrroles (Figure ). Pyridines could also be accessed via a 6- endo cyclization of 90 , while isoquinolines 93 could be accessed following isomerization of a 6- exo cyclized product derived from 92 (Figure ). Sequential Heck cyclization followed by chemical oxidation allowed access to azaazulenes. , This methodology, specifically the use of oxime esters in Heck cyclizations to generate nitrogen heterocycles, is now commonly referred to as a Narasaka–Heck reation …”
Section: Nitrogen Cross-couplingmentioning
confidence: 99%